CRISPR/Cas9-Mediated Targeted Mutagenesis of GmUGT Enhanced Soybean Resistance Against Leaf-Chewing Insects Through Flavonoids Biosynthesis - Zhang, Yongxing; Guo, Wei; Chen, Limiao; Shen, Xinjie; Yang, Hongli; Fang, Yisheng; Ouyang, Wenqi; Mai, Sihua; Chen, Haifeng; Chen, Shuilian; Hao, Qingnan; Yuan, Songli; et al. (Frontiers in Plant Science, 2022)
The leaf-chewing insects have become significant insect pests that cause yield loss and reduced seed quality in soybean (Glycine Max). Breeding soybean varieties resistance to leaf-chewing insects can minimize the need for insecticide use and reduce soybean yield loss and pesticide concerns. In this study, Agrobacterium-mediated transformation introduced the CRISPR/Cas9 expression vector into soybean cultivar Tianlong No. 1 and generated targeted mutants of Glyma.07g110300 gene encoding a UDP-glycosyltransferase (UGT). We obtained two novel types of mutations, 33 bp deletion and one bp insertion at GmUGT coding region, respectively, enhancing resistance to Helicoverpa armigera and Spodoptera litura. In addition, overexpressing GmUGT lines were more sensitive to H. armigera and S. litura in soybean. Both mutations and overexpressing lines exhibited no obvious phenotypic changes. Results of different metabolites and differentially expressed genes suggested that GmUGT altered the flavonoids contents and the expression of genes related to flavonoids biosynthesis and defence response genes to regulate the resistance to leaf-chewing insects. Furthermore, the ectopic expression of the GmUGT gene in the Arabidopsis ugt72b1 mutant substantially rescued the phenotypes of the atugt72b1 mutant in resistance to H. armigera. Our study provided a strategy, and opportunity for increasing resistance to leaf-chewing insects in soybean through CRISPR/Cas9-mediated targeted mutagenesis of UGT genes.